2014
DOI: 10.1016/j.jpor.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Non-randomized controlled prospective study on perioperative levels of stress and dysautonomia during dental implant surgery

Abstract: CgA levels were high in both groups immediately before surgery, and thus CgA values immediately before surgery may not be a reliable indicator of the need for intravenous sedation. Also, spectral analysis of HRV, especially ΔL/H and ΔCCV(HF), could be useful for assessing tension and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
0
11
0
5
Order By: Relevance
“…Some stressors, such as prolonged mental and physical effort, public speaking, examinations, apprehension before surgery [8], [9], can induce an increasing of these stress biomarkers, with pathological consequences on health. One of the most common stressors which workers are often subjected to is the so called “occupational stress”.…”
Section: Introductionmentioning
confidence: 99%
“…Some stressors, such as prolonged mental and physical effort, public speaking, examinations, apprehension before surgery [8], [9], can induce an increasing of these stress biomarkers, with pathological consequences on health. One of the most common stressors which workers are often subjected to is the so called “occupational stress”.…”
Section: Introductionmentioning
confidence: 99%
“…Bilinçli IV (intravenöz) sedasyon yapılan hastaların rahatlığı ve iş birliği, cerrahın operasyona odaklanmasını arttırılabilir (20). Ameliyat öncesi anksiyetesi olan bireylerin stres seviyelerini belirleyecek ve IV sedasyon uygulaması için endikasyon oluşturabilecek geçerli bir parametre şuana kadar bulunamamıştır (29). Sonuç olarak; dental tedaviler ve özellikle ağız cerrahisi işlemleri hastalarda anksiyete oluşma ihtimalini yükseltir.…”
Section: Discussionunclassified
“…Bir çalışmada operasyon öncesi anksiyete skorları, implant cerrahisinde periodontal cerrahiye göre daha yüksek çıkmıştır. Aynı çalışmada tedavisi tekrarlanan hastaların 3. veya 4. defa cerrahi işlem gören hastalara göre daha yüksek anksiyeteye sahip oldukları görülmüştür (29). Anksiyete ile İlişkili Faktörler: Cinsiyetin anksiyete üzerine etkisinin incelendiği çalışmaların dördünde kadınların ve erkeklerin anksiyeteleri arasında farklılık görülmemiştir (18,25,26,28).…”
Section: Anksiyetenin Görülme Sıklığı Tipi Ve Zamanıunclassified
See 1 more Smart Citation
“…However, when comparing HRV before and after surgery in patients who received local anaesthesia with or without intravenous sedation in dental implant surgery, Morino et al 21 observed that HF, LF and LF/HF ratio did not differ between study times (pre-and post-operative).…”
mentioning
confidence: 99%